2019
DOI: 10.1097/meg.0000000000001317
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with a low-FODMAP diet in irritable bowel syndrome: are eating disorders the missing link?

Abstract: Objectives:The low FODMAPs diet has emerged as an option for the treatment of irritable bowel syndrome (IBS). One major challenge of this diet is that it is very restrictive, and compliance is usually low. Preliminary findings suggest an association between eating disorder (ED) and the risk of developing IBS. The primary aim of the study is to assess the correlation between compliance to low FODMAPs diet and risk of eating disorder behaviours among an irritable bowel syndrome cohort. Methods:We report a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 45 publications
1
63
1
3
Order By: Relevance
“…low-FODMAP diet, gluten-free diet) are increasingly discussed as a first-line therapeutic option in IBS management (30). Indeed in a recent IBS study, greater adherence to a low-Fermentable Oligo-, Di-, Mono-saccharides And Polyols (FODMAP) diet was associated with a positive SCOFF (31). Further investigation is required to explore suitable therapeutic options for these patients with a combination of IBS and underlying EDs associated with anxiety or depression and poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…low-FODMAP diet, gluten-free diet) are increasingly discussed as a first-line therapeutic option in IBS management (30). Indeed in a recent IBS study, greater adherence to a low-Fermentable Oligo-, Di-, Mono-saccharides And Polyols (FODMAP) diet was associated with a positive SCOFF (31). Further investigation is required to explore suitable therapeutic options for these patients with a combination of IBS and underlying EDs associated with anxiety or depression and poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Eating disorder behavior was recently evaluated by Mari et al using the SCOFF instrument within a population of adults with irritable bowel syndrome (IBS) who were instructed to begin a low FODMAP diet (5). The included subjects had failed previous IBS interventions (5).…”
mentioning
confidence: 99%
“…It is therefore not improbable that recommending a restrictive diet will prompt or reinforce an eating disorder. Although Mari et al reported that these kinds of patients have greater adherence to an LFD, elimination diets should be avoided in patients with eating disorders, such as orthorexia nervosa and/or avoidant/restrictive food intake disorder [90]. These patients have an obsessive focus on food that compromises their social and work life [91].…”
Section: Precipitating Eating Disorder Behaviormentioning
confidence: 99%
“…It is also mandatory that future studies use common and shared outcome measures in terms of symptom severity scores and quality of life questionnaires, as this will enable a reliable comparison between different studies. It is also to be hoped that in the near future, an easy and reliable tool to assess patients' adherence will be available, especially to evaluate the patients in the medium-and long-term, i.e., during the aLFD period, after the reintroduction phase [90].…”
Section: Hopes For the Futurementioning
confidence: 99%